2016
DOI: 10.1186/s13054-016-1355-9
|View full text |Cite
|
Sign up to set email alerts
|

The Dose Response Multicentre Investigation on Fluid Assessment (DoReMIFA) in critically ill patients

Abstract: BackgroundThe previously published “Dose Response Multicentre International Collaborative Initiative (DoReMi)” study concluded that the high mortality of critically ill patients with acute kidney injury (AKI) was unlikely to be related to an inadequate dose of renal replacement therapy (RRT) and other factors were contributing. This follow-up study aimed to investigate the impact of daily fluid balance and fluid accumulation on mortality of critically ill patients without AKI (N-AKI), with AKI (AKI) and with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 26 publications
2
86
0
5
Order By: Relevance
“…In critically ill patients, apparently excessive fluid overload has a negative association with outcome [16,17] . Such fluid overload appears physiologically undesirable and may participate in the pathogenesis of several clinically important complications like impaired wound healing, prolonged mechanical ventilation, and risk for pulmonary edema [18] .…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…In critically ill patients, apparently excessive fluid overload has a negative association with outcome [16,17] . Such fluid overload appears physiologically undesirable and may participate in the pathogenesis of several clinically important complications like impaired wound healing, prolonged mechanical ventilation, and risk for pulmonary edema [18] .…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…Fluids lead to harm unless; 1) the tissue hypoxia results from inadequate oxygen delivery rather than mitochondrial or microvascular dysfunction and 2) fluid administration leads to an increase in tissue oxygen delivery (1,2,3). Prior debates and investigations have focused on optimal methods for differentiating between states of inadequate oxygen delivery and mitochondrial dysfunction (4,5,6).…”
mentioning
confidence: 99%
“…The lack of these stages of AKI may limit the generalizability of trajectory-based findings to a trauma population with severe AKI. Fourth, previous studies have compared patients with and without AKI and have found an association with fluid accumulation and mortality in AKI [34, 35]. While most patients in the study were likely vigorously hydrated early in their ICU care, in accordance with ICU practice, we lacked accurate fluid balance data.…”
Section: Discussionmentioning
confidence: 98%